Cover Picture: Electrochemically Modified Carbon and Chromium Surfaces for AFM Imaging of Double‐Strand DNA Interaction with Transposase Protein (ChemPhysChem 2/2013). Issue 2 (28th January 2013) - Esnault, Charles; Chénais, Benoît; Casse, Nathalie; Delorme, Nicolas; Louarn, Guy; Pilard, Jean‐François
<x xml:space="preserve">Abstract</x> A simple route for immobilizing linear DNA double‐strands is described on p. 338 by B. Chénais, J.‐F. Pilard et al. Surface modification by electrografting of an aryldiazonium salt yields a roughness of 0.2 nm. The low roughness obtained by the modification permits visualization by AFM of dsDNA and complexes of dsDNA with a protein.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>